The Alzheimer's disease THErapy with NEuroaid (ATHENE) study protocol: Assessing the safety and efficacy of Neuroaid II (MLC901) in patients with mild-to-moderate Alzheimer's disease stable on cholinesterase inhibitors or memantine—A randomized, double-blind, placebo-controlled trial - Chen, C.L.H. (Elsevier Inc, 2021)
10.1016/j.trci.2018.12.001